Population structure as revealed by SNPs in the Iberian honey bee (Apis mellifera iberiensis) - Chávez-Galarza, Julio (2011)
The Honey bee, Apis mellifera L., occurs naturally in Africa, Middle East and Europe. The adaptation to a diversity of ecological conditions has led to evolution of over 24 subspecies. The honey bee subspecies that occurs in the Iberian Peninsula is Apis mellifera iberiensis, which is originated by natural hybridization between lineage A (African) and lineage M (western European). The objective of this study was to unravel the population structure of A. m. iberiensis by carrying out a genome wide analysis using SNPs. Over 711 individuals sampled across three transects (one along the Atlantic Coast, one along the Mediterranean coast, and one central) in the Iberian peninsula were genotyped for 1536 SNPs using the golden gate assay of Illumina. The genetic structure was analyzed by a Bayesian clustering method. It was observed a north – south cline in the three transects and the largest difference was exhibited between the Atlantic populations and the other two transects.